High-sensitivity photonic crystal fiber force sensor based on Sagnac interferometer for weighing. (March 2020) - Liu, Qiang; Xing, Liang; Wu, Zhaoxia; Cai, Lu; Zhang, Zerui; Zhao, Jincheng
Highlights: The high sensitivity is up to 16.32 nm/N as the force varies from 0 N to 0.392 N. We find the sensitivity of the sensor increases as the length of the PM-PCF decreases. The sensor is very weakly affected by ambient temperature. Abstract: Based on Sagnac interferometer, we proposed a force sensor with simple structure by embedding a short of polarization-maintaining photonic crystal fiber (PM-PCF) into Sagnac loop. It can be used to weigh small objects. Experiments were carried out with PM-PCF of different lengths. The results show that as the length of PM-PCF decreases, the sensitivity of the sensor will increase. As the length of PCF is 3 cm, the sensitivity reaches to 16.32 nm/N as the force varies from 0 N to 0.392 N. Due to the ultralow thermal coefficient of the quartz crystal, the force sensor is insensitive to temperature and therefore does not have to be taken into account the effect of temperature on the sensor.